Meta-Analysis Of Guided Inquiry Model On Physics Learning (Universitas Negeri Surabaya, 2020)
Abstract Guided Inquiry is one of the learning models that often used in research into the application of learning models in physics learning. This study aims to analyse the learning process with the Guided Inquiry model and its effect on increasing the students’ competence and skills from previous studies. This research method uses meta-analysis with stages: data collection, data reduction, data display, and drawing conclusions or verification. The secondary data used, that is, data collected indirectly on the object studied in the form of 20 national and international journal articles. The first step in this research is to collects journals, selection 20 journals with the same research design, creates a visualisation in VOSviewer software, and calculates the effect size of the research results. The meta-analysis topic discusses in the research is about to improve students' science skills, school level, subject matter and then the media used. The results of the study state that learning physics using Guided Inquiry model can improve the scientific literacy competencies, critical-thinking skills, and students learning outcomes that measured separately (moderate effect) and simultaneously (modest effect). Another results show that Guided Inquiry model recommended for students that have higher-order-thinking skills, apply with real learning-media, and used for the investigated characteristic content-material. Keywords: Guided Inquiry, physics learning, meta-analysis